DAMPAK PENGELOLAAN HUTAN RAKYAT TERHADAP KONDISI EKONOMI RUMAH TANGGA PETANI (DI DESA SORONALAN, KECAMATAN SAWANGAN, KABUPATEN MAGELANG) (PEOPLES FOREST MANAGEMENT IMPACT TOWARDS THE FARMERS HOUSEHOLD ECONOMIC CONDITIONS: CASE STUDY OF SORONALAN VILLAGE, - VR Ingesti, Pantja Siwi (Jurnal Ilmu-Ilmu Pertanian, 2008)
he research takes place in Soronalan village, Sawangan, Magelang, aiming to find out the influence of peoples forest management towards income, poverty and income distribution among the farmers. The selection of this reseacth location is done by purposive sampling, taking 60 farmers as samples by Proportionate Random Sampling. The samples are classified into two groups, first is the peoples forest with a commodity combination of Sengon (Albizzia falcataria) - Coconut - Grass, and the second is the peoples forest commodity combination of Sengon - Coconut - herbs. The data analysis is done by Gini Ration. The research results indicate that the people forest management can increase the farmer household income, reduce poverty and increase prosperity, and level the income distributions among farmer families.